Are Personality Types Related to Cyberbullying Behavior Trends in Adolescents? - Desi Christin Saragih; Heni Dwi Windarwati; Ayut Merdikawati (Universitas Muhammadiyah Semarang, 2020)
Adolescent growth and development is influenced by 2 factors, namely internal and external factors. Internal factors are factors that influence the fulfillment of developmental tasks originating from within the individual, both physical and psychological, while external factors are factors that influence the fulfillment of developmental tasks originating from outside the individual self. There are several examples of external factors, namely biological and physical environment, psychosocial and depression, family and cultural factors, and economic factors. Psychosocial factors involve psychological and social aspects. The social aspect can be done without having to face to face directly or can be done online using social media. the freedom of a person to use social media causes various abuses of social media, for example cyberbullying. Cyberbullying in adolescents is influenced by several factors, namely personality type, perception of the victim, the role of parent and child interaction. The research aims to determine the relationship of personality types with the tendency of cyberbullying behavior in adolescents. The study was conducted on 10th grade high school teenagers in Malang. The sample was 126 students with a purposive sampling technique. Data was collected using Eysenck Personality Questionare and cyberbullying instruments. Data were analyzed using Chi Square test. There is no significant relationship between personality types and the tendency of cyberbullying behavior in 10th grade teenagers in Malang with Asymp. Sig 0.128 or p-value> ???? (0.05).